Influence of Gender on the Word-of-mouth Process in Restaurant Consumption Using Chronic Regulatory Focus. Issue 5 (3rd September 2022) - Sun, Bongran; Ham, Sunny
ABSTRACT: This study aimed to examine the impact of gender on the word-of-mouth (WOM) process in restaurant consumption by adopting the regulatory focus orientation of consumers as a fundamental factor that affects this process. The study analyzed a total of 361 valid questionnaires collected from restaurant consumers in the US to examine the WOM process. The analysis produced significant empirical evidence. The results revealed that gender plays a significant role in psychological aspects such as personality traits (chronic regulatory focus) and emotion but not in cognitive aspects, including WOM intention. This study makes theoretical contributions by extending the literature on gender, WOM, and regulatory focus. The results also present implications and suggestions for future research.